Penerapan Simple Additive Weighting Dalam Pemilihan Pembelian Mobil Bekas Berpenumpang Menggunakan Tableau Visualization - Permana, Denny Riandhita Arief; Rozi, Muhamad Fahrul; Heriyanto, Lucky; Ismono, Ahlan; Putri, Windy Seirina (Teknik Informatika Fakultas Ilmu Komputer, 2026)
Used passenger cars are an attractive alternative for consumers because they offer more economical prices than new cars, while still maintaining competitive quality. However, the large selection of used cars with various criteria often makes it difficult for prospective buyers to make the right choice. This research was conducted to develop a Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to help prospective buyers choose a used car based on several criteria, namely price, engine capacity, mileage (kilometers), and seating capacity. The data used is used car sales data. T In addition, data visualization through Tableau is also used to provide a clearer and more easily understood information representation for Sentosa Motor. The analysis results show that the SAW method is able to produce objective and accurate recommendations, thus helping prospective Sentosa Motor buyers determine the used car that best suits their needs and preferences